Effect of annealing on the semicrystalline structure of normal and waxy corn starches - Rocha, Thais S. [UNESP]; Felizardo, Suelen Gleice [UNESP]; Jane, Jay-lin; Franco, Celia. M. L. [UNESP] (Elsevier B.V., 2012)
The influence of amylose and amylopectin on structural reorganization occurred during annealing was studied for normal and waxy corn starches. Annealing caused an increase in crystallinity in the waxy corn starch, whereas the number of pores on the granule surface, observed by SEM, increased especially for normal corn starch. Amylose and amylopectin chains of the annealed normal corn starch were degraded to greater extension during enzymatic hydrolysis than those of the native starch. on contrary, the annealing caused a protective effect on waxy corn starch amylopectin toward the enzymatic reaction suggesting that this treatment promoted a better interaction between amylopectin chains of waxy corn starch. The amylose molecules of normal corn starch may have impaired the mobility of amylopectin molecules and restricted the reorganization of the crystalline structure during the annealing. The major increase in pores number on the granule surface of annealed normal corn starch, resulted of the endogenous amylase action during annealing, could facilitate the exogenous enzymes' role in the degradation of the starch granules' amorphous area. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Amylopectin; Amylose; Hydrothermal treatment; Structure